Autophagy, a critical element in the aging male reproductive disorders and prostate cancer: a therapeutic point of view - Pourya Raee; Shing Cheng Tan; Sajad Najafi; Farshid Zandsalimi; Teck Yew Low; Shahin Aghamiri; Elham Fazeli; Mahyar Aghapour; Zahra Shams Mofarahe; Mohammad Hossein Heidari; Fatemeh Fadaei Fathabadi; Farid Abdi; et al. (BMC, 2023)
Abstract Autophagy is a highly conserved, lysosome-dependent biological mechanism involved in the degradation and recycling of cellular components. There is growing evidence that autophagy is related to male reproductive biology, particularly spermatogenic and endocrinologic processes closely associated with male sexual and reproductive health. In recent decades, problems such as decreasing sperm count, erectile dysfunction, and infertility have worsened. In addition, reproductive health is closely related to overall health and comorbidity in aging men. In this review, we will outline the role of autophagy as a new player in aging male reproductive dysfunction and prostate cancer. We first provide an overview of the mechanisms of autophagy and its role in regulating male reproductive cells. We then focus on the link between autophagy and aging-related diseases. This is followed by a discussion of therapeutic strategies targeting autophagy before we end with limitations of current studies and suggestions for future developments in the field.